Comparative Study of Carbon Dioxide and Methane Adsorption by Synthesized Fine Particles of SAPO-34 Molecular Sieve - Sayed Siamak Ashraf Talesh; Shohreh Fatemi; Sayed Jalal Hashemi; Peyman Emrani (Iranian Journal of Chemistry & Chemical Engineering, 2010)
Fine particles Silicoaluminophosphate-34 were synthesized by hydrothermal sol-gel method. The effect of crystallization time, as one of the important synthesis factors on particle size and crystallinity, kinetic and equilibrium adsorption, and selectivity of CO2 / CH4 has been studied in this work. The adsorption isotherms are obtained at moderate gauge pressures (100-3000 kPa) and temperatures (278, 288 and 298 K), and the equilibrium adsorption parameters as well as heat of adsorption are determined for the synthesized SAPO-34. The observed adsorption selectivity of CO2 to CH4 was determined to be around eight for that sample with higher degree of crystallinity.The crystallinity, isotherm parameters, adsorption selectivity and heat of adsorption confirm that the synthesized fine particle of SAPO-34 could be a good candidate for separation of CO2 from CH4.